Synthesis and reactivity of α, ω-homotelechelic polymers by Cu(0)-mediated living radical polymerization. (January 2015) - Simula, Alexandre; Nurumbetov, Gabit; Anastasaki, Athina; Wilson, Paul; Haddleton, David M.
Graphical abstract: Highlights: SET-LRP furnishes α, ω -homotelechelic polymers with high end group fidelity. Retention of both chain ends can be verified either analytically or experimentally. Iterative addition of a comonomer furnishes telechelic block copolymers. Thio-bromine substitution can alter the chain-end functionality and properties. Incorporation of α, ω -hydroxyl groups enables further chain end modification. Abstract: Telechelic poly( n -butyl acrylate) and poly[poly(ethylene glycol) methyl ether acrylate] are obtained with high monomer conversions and narrow molecular weight distributions ( Ð  < 1.2) by Cu(0)-mediated living radical polymerization (SET-LRP). The high end group fidelity of the polymer is confirmed by a combination of 1 H NMR and MALDI-ToF-MS analysis. The reactivity of the telechelics is exploited to yield amphiphilic BAB triblocks, by sequential addition of a second monomer, which self-assemble in water. Furthermore, nucleophilic thiol-bromine substitution using 2-mercaptoethanol post-polymerization enables the incorporation of primary alcohols on both the α- and ω- polymer chain ends. The presence and reactivity of hydroxyl end-groups is confirmed upon reaction with isocyanates and further exploited to induce the ring opening polymerization (ROP) of ε -caprolactone.